Enhancing the photocatalytic efficiency of ZnO thin films by the addition of Mo and rGO. (2022) - Ravichandran, K.; Dhanraj, C.; Mohamed Ibrahim, M.; Kavitha, P.
Abstract: In the present study, ZnO:Mo/rGO thin films were deposited on stainless steel mesh substrates using nebulizer spray method. The photocatalytic efficacy of the ZnO:Mo/rGO film were studied under solar light against two dyes viz . Methylene blue (MB) and Rhodamine B (RhB) and the results were compared with undoped ZnO films and Mo doped ZnO films. The band gap values are found to be 2.71 eV, 2.92 eV and 3.23 eV for ZnO:Mo/rGO, ZnO:Mo and ZnO films, respectively. The ZnO:Mo/rGO film as a photocatalyst is more responsive to visible light than the other two sets of samples. The PL, SEM, XRD and FTIR studies support the discussion on the mechanism behind this improvement.